The Internalization of Prophetic Values in the Poems “Sang Utusan” and “Musim Panen” by Kuntowijoyo - Mukaromah , Umi Roisatul; Ningrum , Asti Tiana; Rabbani, Ilham; Rizky , Auzia Fadhila; Madona , Prita Teresna; Kusuma , Santi Dwi (CV. Tripe Konsultan, 2024)
This study aims to explore the internalization of prophetic values in the poems